"You Feel Very Isolated": Effects of COVID-19 Pandemic on Caregiver Social Connections. (17th December 2021) - Bristol, Alycia A.; Mata, Aaron C.; Mickens, Melody; Dassel, Kara B.; Ellington, Lee; Scammon, Debra; Thompson, Amber; Towsley, Gail L.; Utz, Rebecca L.; Terrill, Alexandra L.
One in five individuals in the United States provides care and support to ill, disabled, and aging family members in the home, leading to feelings of burden, stress, and poor health and well-being. Social support represents an important buffer for family caregivers that allows them to feel less isolated and more positive about their caregiving role. This sequential mixed-methods study aimed to examine the effect of the COVID-19 pandemic on family caregivers' social connections. Eighty-two caregivers completed a web-based survey which comprised of fixed-choice and open-ended questions. Survey data showed that the majority of caregivers (83%) reported an increase in stress and feeling lonely (77%) during the pandemic. Qualitative interviews with a subsample of caregivers ( n =27) further explored social connections during the pandemic. Three themes echoed the quantitative findings and centered around defining boundaries, intentionality in social interactions, and loss of social resources. Although caregivers were often strained by new or increased caregiving demands, many experienced positive changes such as feeling a deeper connection with the care-recipient. Findings from this study highlight the need for further consideration of the impact of social isolation on the well-being of caregivers.